Operational analysis and limitations of the VSI-Based multi-line FACTS controllers - Vasquez-Arnez,R.L. (2006)
In this paper, the operational analysis and the main limitations of the VSI-based multi-line FACTS controllers, namely: the GIPFC (Generalized Interline Power Flow Controller) and the IPFC (Interline Power Flow Controller), are analyzed. The GIPFC & IPFC are amongst the newest devices within the FACTS technology. By utilizing these devices an enhanced and nearly instantaneous controllability over independent transmission systems, can be obtained. The steady-state analysis of a GIPFC & IPFC controlling two balanced independent AC systems, is initially modeled. The use of the instantaneous power theory along with the d-q orthogonal co-ordinates showed to be appropriate tools for assessing the GIPFC response towards the operation of both controlled systems. Yet, to observe its dynamic behavior and simultaneously validate the previous steady-state analysis, a phase-shift VSI-based GIPFC was implemented in the ATP program. Where applicable, a comparative evaluation between the GIPFC and the IPFC, is also presented.